Evoked potentials and abstract thinking - Tatalović Vorkapić, Sanja; Kulenović, Alija; Tadinac, Meri; Buško, Vesna (2008)
The aim of this study was to investigate the relationship between measures (latency and amplitude) of evoked potentials (N1, P2, N2, P3 and SW) elicited by a standard visual oddball paradigm, and abstract reasoning measured by Abstract Reasoning Test (TAM ; Kulenović, 2003). Even though the results of most studies of evoked potentials and intelligence have been inconsistent, and although they were mostly concerned with the relationship between P300 and intelligence, it has been proposed that participants with higher reasoning ability would show significantly shorter latencies of N1, P2 and P3 waves. Because of previously established impact of the experimental task complexity on the relationship between EP amplitude and intelligence, it was not expected for this correlation to be significant, as a very simple standard visual oddball task was used. The sample consisted of 43 participants, all female, right-handers, in the age range 19-23 years. The evoked potentials were recorded in two trials for each participant. Active electrodes were placed on O1, O2, P3 and P4 (according to 10-20 system), and referred to Fz. Significant negative correlation has been found only between N1-wave measured on O1 electrode and results on the Series subtest of TAM. A shorter N1-latency evoked by visual oddball task in participants with higher level of abstract reasoning was expected. This finding is discussed in view of psychological-functional role of N1-wave, information processing demands of specific tasks, perceptive characteristics, and the task complexity level.
Projekt MZOS
Projekt MZOS
ENG